Individual cage housing affects feed intake and induces sex-specific effects on body weight in Japanese quails - Reda, Gebrehaweria K.; Ndunguru, Sawadi F.; Csernus, Brigitta; Lugata, James K.; Knop, Renáta; Szabó, Csaba; Czeglédi, Levente (Acta Agraria Debreceniensis, 2024)
Individual cage housing in poultry production could be a potentially stressful environment for the birds that can alter feed intake, consequently induce negative effects on performance. Previous studies used individual bird-based experiments to extract the detailed molecular, physiological, and fitness outcomes of treatments. Understanding sex-specific effects of isolation on social birds such as Japanese quails (Coturnix japonica) may reveal important considerations. To understand this phenomenon, birds were kept in groups of 10 for one week and they were kept in individual cages for another week.  Daily feed intake (DFI) was measured each day and body weight was measured at the beginning, middle, and end of group rearing and at the beginning and end of individual rearing. It was found that both males and females showed a reduction DFI in response to individual rearing (p